In vivo calibration of a subcutaneous glucose sensor for determination of subcutaneous glucose kinetics - Velho, G.; Froguel, P.; Thevenot, D.R.; Reach, G. (Diabetes, Nutrition and Metabolism – Clinical and Experimental, 1988)
The aim of this work was to develop a method for calibrating in vivo a subcutaneous glucose sensor; this calibration procedure was used to investigate the kinetics of the estimated subcutaneous glucose concentration during variations in blood glucose level. These experiments were performed in anaesthetized rats: 1) In 25 animals, glycaemia was decreased from 5.8 ± 0.2 to a 2.9 ± 0.2 mmol/l plateau, following the intravenous injection of 1 unit of insulin. This drop was followed by a decrease in the signal amplitude with a 5 min time lag, from 13.54 ± 1.09 to 10.28 ± 1.05 nA (p < 0.01); 2) These two steady states allowed to perform a two-point in vivo calibration of the sensor and to calculate the apparent subcutaneous glucose level during subsequent glucose administration: a) Following a continuous glucose infusion (n = 6) that increased glycaemia within 35 min to a 5.6 ± 0.4 mmol/l plateau, the subcutaneous glucose level increased to a 5.1 ± 0.2 mmol/l plateau (NS); when glycaemia was increased to 11.3 ± 0.3 mmol/l (n = 7), subcutaneous glucose concentration raised to 10.7 ± 0.4 mmol/l (NS); b) In contrast, after a glucose bolus (n = 7), the glycaemia peak at 2 min was 12.4 ± 0.9 mmol/l, while the subcutaneous glucose peak, observed at 2 min, was only 6.2 ± 0.6 mmol/l (p < 0.01). We conclude, therefore, that under steady state conditions, the apparent subcutaneous glucose concentration reflects blood glucose level, thus validating the subcutaneous tissue as a site for the implantation of a glucose sensor to be used in a closed-loop insulin delivery system.